2022
DOI: 10.12775/jehs.2022.12.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The sense of coherence and the health behavior of students medical and non-medical universities

Abstract: The article presents the sense of coherence in the perspective of health behaviors of students of medical and non-medical universities. The first part introduces the concepts of the sense of coherence and health-related behaviors. The sense of coherence was explored using the Life Orientation Questionnaire (SOC-29), and health behaviors with the Health Behavior Inventory (IZZ). The group taking part in the study consisted of 216 people - 90 students of medical universities and 126 students of non-medical unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, a study conducted by researchers from Szczecin showed that students of medical and non-medical universities differed in terms of the declared health behaviors. Medical college students had a higher severity of health behaviors [14]. A study comparing the health behaviors of first-year students living in family homes and moving from home to study was also conducted.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study conducted by researchers from Szczecin showed that students of medical and non-medical universities differed in terms of the declared health behaviors. Medical college students had a higher severity of health behaviors [14]. A study comparing the health behaviors of first-year students living in family homes and moving from home to study was also conducted.…”
Section: Discussionmentioning
confidence: 99%